Nanodisc‐Mediated Conversion of Virustatic Antiviral Antibody to Disrupt Virus Envelope in Infected Cells (Small Methods 4/2022). Issue 4 (18th April 2022) - Hwang, Jaehyeon; Jung, Younghun; Moon, Seokoh; Yu, Seokhyeon; Oh, Hyunseok; Kim, Soomin; Kim, Kyeong Won; Yoon, Jeong Hyeon; Chun, Jihwan; Kim, Sang Jick; Chung, Woo‐Jae; Kweon, Dae‐Hyuk
Abstract : Back Cover In article number 2101516, Dae‐Hyuk Kweon and co‐workers show that the cooperation of antibodies and nanodiscs disrupts the influenza virus inside infected cells. This cooperation provides the virus‐infected host cells with the ability to self‐eliminate the virus.